Biobriquettes from Rice Husks Using Molasses and Egg White Adhesives with Variations in Adhesive Concentration - Hadryza Anduanda Zahra; Elvianto Dwi Daryono (Universitas Islam Raden Rahmat, Malang, 2025)
The use of rice husks as a raw material for briquettes helps reduce agricultural waste while providing added economic value to the product. Molasses is a by-product of the sugar-making process, which is abundant and often not utilized optimally. Molasses has the advantage of being a biobriquette adhesive because it is relatively cheap, easily biodegradable, and environmentally friendly. Albumin in egg white has the ability to form a gel when heated or dried, so it can potentially help bind biomass particles such as rice husks compared to other adhesives. The research operating conditions include raw materials, namely rice husk, carbonization temperature of 300℃, carbonization time of 1 hour, briquette size ≥ 150 mesh, type of adhesive (molasses and egg white) and adhesive concentration (12%, 13%, 14%, 15%, 16%, 17%, 18% and 19%). The optimum conditions were obtained by using 15% egg white adhesive, namely with a water content of 8%, ash content of 7%, volatile matter content of 1.5%, and bound carbon content of 83.5% which met SNI 01-6235-2000 and a calorific value of 4194.03 cal/g, and a combustion rate of 0.140 g/minute.